Analysis of the use of Recycle to Increase the Productivity of Msmes Ecofriendly Board Waste Bank in Medan Village, Belawan I - Meutia Nanda; Adinda Aulia Ar-ramdhani; Putri, Dian Yustika; Dhidy Haz Idiano; Syahrani Lubis (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Waste is still a common problem in society. Management of inorganic waste in the form of plastic waste and banners is more difficult to decompose so it remains as waste for a long time and causes environmental pollution. There are various ways to overcome this problem, namely 3R (Reduce, Reuse, Recycle). Medan Belawan I Subdistrict is one of the areas in Medan City that has coordinated the commercial use of inorganic waste. One of the perpetrators of waste utilization in this area is the Ecofriendly Board Waste Bank. This research aims to analyze waste banks to increase the productivity of MSMEs by the Ecofriendly Board in Medan Belawan I Subdistrict. The management of plastic waste and banners gets high added value because it is processed into material for making furniture as one of the initial goals of increasing the productivity of the community and MSMEs. The research method uses a qualitative approach with descriptive research methods. The results of this research, with a recycling system that is carried out continuously on a mass scale, can minimize waste and increase the productivity of MSMEs. It was concluded that the existence of recycling activities made it possible to slightly reduce the huge amount of waste. It is recommended that more waste banks or similar institutions be established in various regions to support MSMEs in utilizing recycled materials for their production.